Pedagogies in the Flesh Case Studies on the Embodiment of Sociocultural Differences in Education (Springer International Publishing, 2018)
This book presents a collection of vivid, theoretically informed descriptions of flashpoints--educational moments when the implicit sociocultural knowledge carried in the body becomes a salient feature of experience. The flashpoints will ignite critical reflection and dialogue about the formation of the self, identity, and social inequality on the level of the preconscious body. .